Tobacco use during cannabis cessation: Use patterns and impact on abstinence in a National Drug Abuse Treatment Clinical Trials Network study - McClure, Erin A.; Baker, Nathaniel L.; Sonne, Susan C.; Ghitza, Udi E.; Tomko, Rachel L.; Montgomery, LaTrice; Babalonis, Shanna; Terry, Garth E.; Gray, Kevin M. (Drug and alcohol dependence, 2018)
•The impact of nicotine dependence on cannabis outcomes was examined.•Tobacco co-use was lower in this sample compared to national averages.•Those with lower nicotine dependence reduced their smoking during active treatment.•Nicotine dependence severity did not affect cannabis cessation outcomes.•Nicotine dependence may impact tobacco substitution during cannabis treatment. It is common for cannabis users to also use tobacco. While data suggest that tobacco users have more difficulty achieving cannabis cessation, secondary analyses of clinical trial data sets may provide insight into the moderating variables contributing to this relationship, as well as changes in tobacco use during cannabis treatment. Those were the aims of this secondary analysis. The parent study was a multi-site trial of N-acetylcysteine for cannabis dependence conducted within the National Drug Abuse Treatment Clinical Trials Network. Participants were treatment-seeking adults (ages 18–50) who met criteria for cannabis dependence (N = 302). For cigarette smokers (n = 117), tobacco use was assessed via timeline follow-back and nicotine dependence was assessed via the Fagerström Test for Nicotine Dependence (FTND). Outcome measures included: 1) changes in tobacco use based on treatment assignment, nicotine dependence, and concurrent cannabis reduction/abstinence, and 2) independent associations between nicotine dependence and cannabis abstinence. Cigarette smokers accounted for 39% of the sample (117/302), with a median FTND score of 3.0 (10-point scale). Among those with lower baseline nicotine dependence scores, cigarette smoking was reduced in the active treatment group compared to placebo. Those with moderate/high levels of nicotine dependence showed slight increases in smoking following active treatment. Nicotine dependence did not affect cannabis cessation. Cigarette smoking during cannabis treatment was affected, but depended on baseline nicotine dependence severity, though dependence levels did not impact cannabis abstinence. Interventions that address both tobacco and cannabis are needed, especially due to an increasing prevalence of cannabis use.